Hubungan Efikasi Diri dengan Kreatifitas Kerja Guru Pegawai Negeri Sipil (PNS) Sekolah Dasar Negeri Se-Kecamatan Cibungbulang - Handayani Nurul Hikmah; Ima Rahmawati; Hana Lestari (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
Teacher work creativity is the process of developing all creations and the creation of new works and ideas that are unique and different from the previous ones that can be used by teachers in the learning process. This study aims to determine the relationship between self-efficacy and teacher work creativity. This research was conducted in SDN’s throughout Cibungbulang district. This study uses a quantitative approach with a sample of 78 respondents. The data collection technique used a closed questionnaire with a Likert scale as a measure. The data analysis method used was descriptive analysis and simple linear regression using the help of the SPSS version 20 application. Based on the results of the study, there was a significant positive relationship between self-efficacy and teacher work creativity. This study develops previous research by Sumiyati 2018 entitled the relationship between creativity and the performance of high school chemistry teachers in Jabodetabek.